Answer:
The fourth option is the correct answer
Step-by-step explanation:
The given expression is
-2n(5+n-8-3n)
Given that n=3,We substitute the value of n into the expression and simplify.
This implies that,
-2n(5+n-8-3n)=-2(3)[5+3-8-3(3)]
=-6(5+3-8-9)
=-6(-9)
=54
Hence the answer is 54
Answer:
THE ANSWER IS THIS FOR THE QUESTION UP TOP
Answer:
The answer is 7
Step-by-step explanation:
25 times 25=625
24 time 24=576
625-576=7
And the square root of 49 is 7.
Answer:
3
Step-by-step explanation: There are 3 terms there